Fuzzy pairwise regular bitopological spaces in quasi-coincidence sense (Journal of Bangladesh Academy of Sciences, 2021)
This paper introduces three notions of fuzzy pairwise regular between bitopological spaces in quasi-coincidence sense. Then, we investigate some relations between ours and other counterparts. We observe that all these concepts are preserved under one-one, onto, fuzzy closed, fuzzy open, and fuzzy continuous mappings. Also, the hereditary property is satisfied by these concepts.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 139-143, 2020